Worlding cities Asian experiments and the art of being global - Roy, Ananya; Ong, Aihwa (Studies in urban and social change)
"From Dubai to Delhi and from Singapore to Shanghai, cities across Asia are sites of intense experiments with different ways of being global. This book intervenes in urban theory focused on established global cities, and instead argues that the urban globality is something that is continually being imagined, assembled, and contested. Greater Asia is a region of vibrant innovations in urban design, built forms, governance, aesthetics, and politics. Worlding Cities draws attention to diverse projects of 'worlding' and "reworlding" that draw upon local and transnational relationships. Alternative ways of being global are instantiated through practices of mobility, modeling, and speculation that inter-reference other Asian sites. As many of the essays in this book illustrate, different Asian futures are being shaped in cities, from green governmentality to eco-city, from corporate speculations to political contestations over urban development, from "world-class" city branding to demands for "world-class" services, and from sky-high hopes to dashed dreams on the ground for city-dwellers and migrants. This inter-generation and interdisciplinary group of authors offers the first serious examination of diverse actors, energies, and conditions at play in defining new worlds of inter-Asian urbanism"--Provided by publisher.